Gerásimo Sosa and Chulucanas Handmade Pottery - Puig Tarrats, Esteban (Mercurio Peruano, 2018)
Gerásimo Sosa's handmade pottery constitutes a surprising artistic and cultural legacy due to their shapes and colors. It is inspired by ceremonial pieces as well as utilitarian pottery that was also offered in tombs by the ancient Peruvians but is also a new creation that has given rise to a great artistic tradition.